Nomad Jellyfish Rhopilema nomadica Venom Induces Apoptotic Cell Death and Cell Cycle Arrest in Human Hepatocellular Carcinoma HepG2 Cells - Mohamed M. Tawfik; Nourhan Eissa; Fayez Althobaiti; Eman Fayad; Ali H. Abu Almaaty (Molecules, 2021)
Jellyfish venom is a rich source of bioactive proteins and peptides with various biological activities including antioxidant, antimicrobial and antitumor effects. However, the anti-proliferative activity of the crude extract of Rhopilema nomadica jellyfish venom has not been examined yet. The present study aimed at the investigation of the in vitro effect of R. nomadica venom on liver cancer cells (HepG2), breast cancer cells (MDA-MB231), human normal fibroblast (HFB4), and human normal lung cells (WI-38) proliferation by using MTT assay. The apoptotic cell death in HepG2 cells was investigated using Annexin V-FITC/PI double staining-based flow cytometry analysis, western blot analysis, and DNA fragmentation assays. R. nomadica venom displayed significant dose-dependent cytotoxicity on HepG2 cells after 48 h of treatment with IC50 value of 50 μg/mL and higher toxicity (3:5-fold change) against MDA-MB231, HFB4, and WI-38 cells. R. nomadica venom showed a prominent increase of apoptosis as revealed by cell cycle arrest at G2/M phase, upregulation of p53, BAX, and caspase-3 proteins, and the down-regulation of anti-apoptotic Bcl-2 protein and DNA fragmentation. These findings suggest that R. nomadica venom induces apoptosis in hepatocellular carcinoma cells. To the best of the authors’ knowledge, this is the first scientific evidence demonstrating the induction of apoptosis and cell cycle arrest of R. nomadica jellyfish venom.